Empowering the Past, Confronting the Future: The Duna People of Papua New Guinea - Strathern, Andrew J. author. aut Link
XI, 190 p. 17 illus.
Keywords: How have the Aluni Valley Duna people of Papua New Guinea responded to the challenges of colonial and post-colonial changes that have entered their lifeworld since the middle of the Twentieth-Century? Living in a corner of the world influenced by mining companies but relatively neglected in terms of government-sponsored development, these people have dealt creatively with forces of change by redeploying their own mythological themes about the cosmos in order to make claims on outside corporations and by subtly combining features of their customary practices with forms of Christianity, attempting to empower their past as a means of confronting the future.